Antifungal benzo[b]thiophene 1, 1-dioxide IMPDH inhibitors exhibit pan-assay interference (PAINS) profiles. Issue 20 (1st November 2018) - Kummari, Lalith K.; Butler, Mark S.; Furlong, Emily; Blundell, Ross; Nouwens, Amanda; Silva, Alberto B.; Kappler, Ulrike; Fraser, James A.; Kobe, Bostjan; Cooper, Matthew A.; Robertson, Avril A.B.
Graphical abstract: Abstract: Fungi cause serious life-threatening infections in immunocompromised individuals and current treatments are now complicated by toxicity issues and the emergence of drug resistant strains. Consequently, there is a need for development of new antifungal drugs. Inosine monophosphate dehydrogenase (IMPDH), a key component of the de novo purine biosynthetic pathway, is essential for growth and virulence of fungi and is a potential drug target. In this study, a high-throughput screen of 114, 000 drug-like compounds against Cryptococcus neoformans IMPDH was performed. We identified three 3-((5-substituted)-1, 3, 4-oxadiazol-2-yl)thio benzo[ b ]thiophene 1, 1-dioxides that inhibited Cryptococcus IMPDH and also possessed whole cell antifungal activity. Analogs were synthesized to explore the SAR of these hits. Modification of the fifth substituent on the 1, 3, 4-oxadiazole ring yielded compounds with nanomolar in vitro activity, but with associated cytotoxicity. In contrast, two analogs generated by substituting the 1, 3, 4-oxadiazole ring with imidazole and 1, 2, 4-triazole gave reduced IMPDH inhibition in vitro, but were not cytotoxic. During enzyme kinetic studies in the presence of DTT, nucleophilic attack of a free thiol occurred with the benzo[ b ]thiophene 1, 1-dioxide. Two representative compounds with substitution at the 5 position of the 1, 3, 4-oxadiazole ring, showed mixed inhibition in the absence of DTT. Incubation of these compounds with Cryptococcus IMPDH followed by mass spectrometry analysis showed non-specific and covalent binding with IMPDH at multiple cysteine residues. These results support recent reports that the benzo[ b ]thiophene 1, 1-dioxides moiety as PAINS (pan-assay interference compounds) contributor.